Kajian Tentang Kebudayaan Islam di Kota Jambi - Eka Atmasari, Aninda Salma Rahmawati, Junita Yosephine Sinurat (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2025)
This research aims to identify Islamic culture in Jambi City. The method used in this research is a method that contains 4 stages of research types, namely, Heuristic, Source Criticism, Interpretation and Historiography. The type of source used in writing the research is secondary sources obtained from the results of library studies using historical analysis techniques using interpretation in history which includes books, documents and journals related to Islamic Culture in Jambi City. The results of this research show that Islam entered this area in 1460 AD, or around the 15th century AD. The bearer was an Arab merchant named Ahmad Salim, who later became known as "Datuk Paduka Berhala". He married a Jambi king named Mama, who was known as "Princess Selaras Pinang MasakHistory records that several Islamic boarding schools have been established since the early 20th century AD. Not only Islamic boarding schools, the legacy and culture of Islamic influence in Jambi City include religious ritual traditions in the form of commemorations of Assyura (Syuro), Burdah, Nginau, Nuak Ketan, and so on.